15c-7(-11c-13)=-3(-18c-5)

Simple and best practice solution for 15c-7(-11c-13)=-3(-18c-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15c-7(-11c-13)=-3(-18c-5) equation:



15c-7(-11c-13)=-3(-18c-5)
We move all terms to the left:
15c-7(-11c-13)-(-3(-18c-5))=0
We multiply parentheses
15c+77c-(-3(-18c-5))+91=0
We calculate terms in parentheses: -(-3(-18c-5)), so:
-3(-18c-5)
We multiply parentheses
54c+15
Back to the equation:
-(54c+15)
We add all the numbers together, and all the variables
92c-(54c+15)+91=0
We get rid of parentheses
92c-54c-15+91=0
We add all the numbers together, and all the variables
38c+76=0
We move all terms containing c to the left, all other terms to the right
38c=-76
c=-76/38
c=-2

See similar equations:

| 2x²-30=-7x | | 110x+34x=144 | | -4(b-1)=-28 | | 48=8x+80 | | 2=m+1/2 | | 7c+6=4c-9 | | 9×(x-7)=3² | | -18-19+8y=5y-1 | | 4n-1=-15 | | 3(j-6)+12=-16+4j | | -4x+3=-x-27 | | v/8-4=4 | | 200+20x=1.98 | | 40t=28 | | 4m=5m-14 | | 5y-8=7-6 | | -10=2x+14 | | 2z+12=15 | | -2(u+6)=-4u-22 | | -19=-4-5m | | 180+x+(x-60)=360 | | -13.8=v/5-1.3 | | (2x+30)°=135 | | 2(4x+6)=-36+16 | | 140=7(-4-6x) | | 4000=50+32x | | -3v-7=-34 | | 9x+7=3(3x+5) | | g3+5=7 | | 3x6=-x-18 | | -3b-16b=19 | | 3-m/8=4-m/6 |

Equations solver categories